Grenzen.Gänge.Zwischen.Welten. Kontroversen - Entwicklungen - Perspektiven der Inklusionsforschung - Schimek, Bernhard; Kremsner, Gertraud; Proyer, Michelle; Grubich, Rainer; Paudel, Florentine; Grubich-Müller, Regina (Verlag Julius Klinkhardt, 2021)
The thematic anthology is based on the conception of the 'IFO2020' in Vienna - the 34th annual conference of inclusion researchers - and represents the attempt to present in a bundled form the questions and discussions that have begun around this conference, have been further developed, or perhaps even emerged in this context in the first place. In keeping with the theme of the volume, inclusion research itself necessarily becomes the focus of debate when its inherent controversies, perspectives, and developments are discussed. This results, among other things, in references to empirical, theoretical, and paradigmatic orientations of inclusion, interdisciplinary associations, critiques of both pedagogical and (one's own) academic practice, intersectional interweavings, or even voids that remain open to discussion.